Winning and Losing Relationship: A New Method of University Ranking in the Case of Countries along the Belt and Road - Jin Liu; Songyue Lin; Manling Wu; Wenjing Lyu (Complexity)
From the perspective of the complex system, university ranking is a complex system that involves multiagent actors, which evolve over time. Yet, current major university rankings fail to reflect the system dynamics of the university innovation system. In this paper, we apply the complex system model in the field of the university innovation system in the context of university ranking in the countries along the Belt and Road, which is a long-term overlooked field. We introduce a new method of university ranking based on the “winning and losing” relationship to measure the relative competitiveness between universities. This paper contributes to complex system research, the Belt and Road research, and the university ranking arena.